Knowing who and knowing how : two ways to understand reference - Dahl, Niklas ; 0000-0001-9157-594X (Synthese, 2025)
In this paper I’m concerned with the functional role of singular terms and how it can be used to construct a pragmatist theory of what it takes to understand reference. I argue that there are, at least, two distinct functions which singular terms fulfil, what I will call the talking-about and picking-out functions respectively. Both are, in one sense, ways that a term aids our understanding by specifying who or what a sentence is about, but they come with different requirements for being understood. To illustrate the distinction, I draw on examples from the literature on reference which give rise to very different intuitions about what it takes to understand a singular term. Finally, I argue that this leads to a parallel distinction between two kinds of knowledge-who, depending on which function we are said to know-who with respect to. For the talking-about case, a version of the standard account is sufficient. But to understand an utterance of a singular term with respect to the picking-out function, we need knowledge-who in the sense of knowing how to find what’s referred to sufficiently well to perform a contextually specified action.
Keywords: Knowledge-Who; Reference; Understanding-First